2013
DOI: 10.4103/2279-042x.114084
|View full text |Cite
|
Sign up to set email alerts
|

Factors effective on medication errors: A nursing view

Abstract: Objective:Medication errors are the most common medical errors, which may result in some complications for patients. This study was carried out to investigate what influence medication errors by nurses from their viewpoint.Methods:In this descriptive study, 150 nurses who were working in Qazvin Medical University teaching hospitals were selected by proportional random sampling, and data were collected by means of a researcher-made questionnaire including demographic attributes (age, gender, working experience,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 30 publications
4
21
0
3
Order By: Relevance
“…According to the results of the current study, poor lighting was the most important environmental factor contributing to medication errors from the nurses' point of view. It was consistent with the results of Shahrokhi et al [28]. However, in the study by Bijani et al poor lighting was reported as the least important factor of medication errors [29].…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of the current study, poor lighting was the most important environmental factor contributing to medication errors from the nurses' point of view. It was consistent with the results of Shahrokhi et al [28]. However, in the study by Bijani et al poor lighting was reported as the least important factor of medication errors [29].…”
Section: Discussionsupporting
confidence: 92%
“…Among all the studies analyzed, the greatest emphasis was given to medication errors, [13][14][15][16][17][18][19][20][22][23][29][30][31][32][33][34][35][37][38]40,[42][43] this is due to the choice of studies that recommended analyzing the errors done by the nursing team, who are mainly responsible for this activity. Falls were reported in four studies, but with less incidences.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various ways to avoid errors, the following were highlighted: -Improvements in the nursing work process, understanding it as complex, hampered by working conditions, especially due to the high demand for care, work overload and insufficient remuneration; [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] -Continuing education at work as an effective method to prevent adverse events; …”
Section: Prevention and Methods To Avoid Errorsmentioning
confidence: 99%
See 2 more Smart Citations